(untitled) (Universal International Scientific Journal, 2026)
This article studies the impact of media information on reading culture in the context of a developing digital society. It analyzes changes in reading practice, the features of text perception in the media environment, and the changing role of books and reading in the system of cultural values. Both destructive and constructive aspects of the impact of media information on reading culture are studied. The need to develop media literacy and form a stable motivation for meaningful reading is justified.